2001
DOI: 10.4081/jlimnol.2001.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Lake Orta sediments

Abstract: Lake Orta (18.2 km2, 1.3 km3, 143 m max. depth) has been severely polluted since industrialisation of its watershed began in 1926, at which time the lake began to receive industrial effluents containing high concentrations of copper and ammonia. Chromium-, nickel-, and zinc-rich effluents from plating factories have also contributed to pollution levels, and pH -levels dropped below 4.0 as a result of the oxidation of ammonia to nitrates. More than 60 papers have documented the evolution of the chemical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
2
22
1
1
Order By: Relevance
“…1) corresponding to the area which was primarily affected by industrial discharges of the Bemberg factory since 1926 (Bonacina, 2001;Baudo and Beltrami, 2001). Average population density was 3.9 ind.…”
Section: Resultsmentioning
confidence: 99%
“…1) corresponding to the area which was primarily affected by industrial discharges of the Bemberg factory since 1926 (Bonacina, 2001;Baudo and Beltrami, 2001). Average population density was 3.9 ind.…”
Section: Resultsmentioning
confidence: 99%
“…Sedimentary records of the pollution of Lago Maggiore with DDT, trace metals (especially mercury) and persistent organic pollutants (POPs) over the past ca 55 years have been obtained through the analysis of short cores collected during several sampling campaigns starting in 1963 (e.g., Muntau 1981;Provini et al 1995;Guzzella et al 1998;Baudo et al 2002). Detailed distribution maps for macro and trace elements have been drawn up based on the core data (Baudo et al 1981;Viel and Damiani 1985;Rossi et al 1993;Baudo et al 2002;Bettinetti et al 2005;Guzzella et al 2007) and the total burdens of metals and POPs in sediments have been esti- mated (Cenci et al 1991;Provini et al 1995;Guzzella, unpublished data).…”
Section: Chemical Contaminants: Trace Metals and Organochlorine Compomentioning
confidence: 99%
“…Detailed distribution maps for macro and trace elements have been drawn up based on the core data (Baudo et al 1981;Viel and Damiani 1985;Rossi et al 1993;Baudo et al 2002;Bettinetti et al 2005;Guzzella et al 2007) and the total burdens of metals and POPs in sediments have been esti- mated (Cenci et al 1991;Provini et al 1995;Guzzella, unpublished data). All work to date shows mercury (and other trace metals not shown) and DDT at highest concentrations in sediments deposited during northern Italy's industrial and economic boom of the 1960s (Fig.…”
Section: Chemical Contaminants: Trace Metals and Organochlorine Compomentioning
confidence: 99%
“…Particularly important, also in relation to the effect on the benthic fauna, is the quality of lake sediments: recent studies revealed the presence of toxic residues in the top layer of Lake Orta sediments, which could potentially act as a source of metals to the water column (Baudo and Beltrami, 2001). The presence of trace metals in the sedi-N o n -c o m m e r c i a l u s e o n l y ments also prevent a full recolonization by macrobenthic organisms (Nocentini et al, 2001).…”
Section: Long-term Chemical Changes In Lake Ortamentioning
confidence: 99%